Association of Level Serum Ferritin and Lung Function in Pediatric with Transfusion – Dependent Thalassemia - Putri Nahrisa Nasution; Bidasari Lubis; Ririe Fachrina Malisie; Juliandi Harahap; Wisman Dalimunthe; Hendri Wijaya (GLOBAL HEALTH SCIENCE GROUP, 2026)
Pulmonary dysfunction in children with thalassemia can be restrictive, obstructive, or diffusion impairment. Elevated serum ferritin levels are a cause of pulmonary dysfunction in transfusion-dependent thalassemia patients. The aim of this study was to assess relationship between serum ferritin levels and pulmonary dysfunction in transfusion-dependent thalassemia patients. This cross-sectional study was conducted on 44 transfusion-dependent thalassemia children between May and June 2025 at the Thalassemia Clinic of Adam Malik Hospital, Medan. Demographic characteristics were obtained from interviews and medical records. Lung function was assessed using a spirometer. Associations were analyzed using Shapiro Wilk, Kruskal-Wallis test, and multinomial logistic regression test. A total of 17 children (38.6%) had normal lung function, while 27 children (61.3%) had impaired lung function. Restrictive impairment was present in 24 children (54.5%), and obstructive impairment in 3 children (6.8%). Analysis showed significant differences in serum ferritin levels and splenomegaly in relation to impaired lung function, with p-values of <0.001 and 0.013, respectively. Each 1 ng/mL increase in ferritin levels increased the likelihood of developing restrictive and obstructive pulmonary dysfunction by 0.2% (OR = 1.002; 95% CI: 1.001–1.003). However, gender, hepatomegaly, and duration of transfusion did not show significant differences.